Re-assessing the role of trade policy and import substitution industrialization: Empirical evidence from Pakistan - Ghulam Muhammad Qamri; Shamrez Ali; Tariq Bashir; Muhammad Asim Saeedi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
Researchers and policymakers are re-examining the idea of import substitution industrialization (ISI). Consequently, trade policy has emerged as an essential instrument for promoting ISI. This research looks at the effect of trade policy on ISI, breaking down how tariff rates impact domestic industry by utilizing information from Pakistan in the range of 1998 and 2022. To empirically examine the impact that tariff rates have on ISI, the current research and makes use of Granger Causality, the vector autoregressive (VAR), and the autoregressive distributed lag model (ARDL), as well as the unit root with structural break technique in EViews. The findings show a conclusive two-way connection between tariff rates and ISI. In addition, although an initial increase in tariff rates increases ISI, a subsequent decrease in ISI quickly offsets this effect. Additionally, ISI suffers shortterm and long-term consequences from rising tariff rates. These findings highlight the necessity of gradual integration into global markets for long-term sustainability, despite the initial industrial development fostered by trade protectionism.
Keywords: 330; Import substitution industrialization; trade policy; tariff rate; real effectiveexchange rate; political stability; foreign direct investment